The Relevance of Accounting Theory on Business Financial Performance in Nigeria - Augustine E., Osho,; Adeniyi, Adebambo (European Scientific Journal, ESJ, 2018)
The study was on the relevance of accounting theory on business financial performance in Nigeria. The objective of the study was to examine how accounting theory affects financial performance of business in Nigeria. The research was carried out, using three quoted companies (Berger Paint, Lafarge Cement and Meyer Plc) as the study area. Secondary data was gotten from the companys’ audited annual reports on return on asset with multiple regression analysis. Findings revealed that accounting theory have no significant relationship with the financial performance of business organizations in Nigeria. Thus, it is recommended that the Management of quoted companies must introduce new accounting theories to improve their financial reporting quality and performance; so that the level of their profit can significantly increase.